STUDIES ON THE EFFECT OF COMPOUNDED FEEDS ON THE GROWTH OF JUVENILE BANANA PRAWN PENAEUS MERGUIENSIS - CHANDGE, M. S. (Journal of Indian Fisheries Association, 2015)
Laboratory experiments were conducted to determine the effect ofcompounded feeds on growth of juveniles (3 to 4 em) of the Banana prawnPenaeus merguiensis. In all, seven diets were prepared with differentcombinations of locally available ingredients. Diascure, a local tuber wasused as source of carbohydrate and vitamin mineral mixture (1 %) was usedin all the diets. The results indicated that diets with groundnut cake (diet2,3,5 and 7) produced better survival and growth. In diets 4 and 6 growthwas good but survival was very poor. Amongst all the diets, diet-7 producedsignificantly better growth, survival and food conversion ratio.